2013
DOI: 10.1002/hep.26315
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-140-5p suppresses tumor growth and metastasis by targeting transforming growth factor β receptor 1 and fibroblast growth factor 9 in hepatocellular carcinoma

Abstract: By comparing the expression profiles of microRNAs (miRNAs) in different hepatocellular carcinoma (HCC) subtypes, we identified miR-140-5p as an HCC-related miRNA. We found that miR-140-5p was significantly decreased in HCC tissues and all of six liver cancer cell lines examined and its expression levels were correlated with multiple nodules, vein invasion, capsular formation, and differentiation, as well as overall and disease-free survival of HCC. We also found that miR-140-5p suppressed HCC cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
214
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(234 citation statements)
references
References 38 publications
20
214
0
Order By: Relevance
“…In our study, we found that the weight and length growth, weight ratio of the left hemisphere to the right hemisphere and the rate of reaching standard were all increased; however, decreases were recorded for total response times, total response duration and neuronal apoptosis rate in the hippocampus, when HIBD rats had been treated with DEX + miR‐140‐5p mimics or si‐Wnt1. A previous study has demonstrated that miR‐140‐5p inhibits the MAPK signalling pathway in hepatocellular carcinoma 39. DEX has also been demonstrated to protect the brain against isoflurane‐induced neuroapoptosis in the hippocampus of neonatal rats by suppressing the p38MAPK signalling pathway 40.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that the weight and length growth, weight ratio of the left hemisphere to the right hemisphere and the rate of reaching standard were all increased; however, decreases were recorded for total response times, total response duration and neuronal apoptosis rate in the hippocampus, when HIBD rats had been treated with DEX + miR‐140‐5p mimics or si‐Wnt1. A previous study has demonstrated that miR‐140‐5p inhibits the MAPK signalling pathway in hepatocellular carcinoma 39. DEX has also been demonstrated to protect the brain against isoflurane‐induced neuroapoptosis in the hippocampus of neonatal rats by suppressing the p38MAPK signalling pathway 40.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-16, miR-494-3p, and miR-184 regulate glioma cell proliferation, invasion, and apoptosis and do so by differential mechanisms that target oncogenes or anti-oncogenes and by mechanisms that have been demonstrated in a xenograft animal model. [7][8][9] In this study, we found that miR-140-5p suppressed progression of human tongue cancer, hepatocellular carcinoma, and colorectal cancer [10][11][12] -processes that have not previously been investigated extensively. Specifically, there is an absence of previously published data that have demonstrated the contributions of miR-140-5p in the development of glioma.…”
Section: Introductionmentioning
confidence: 68%
“…13 Emerging evidence suggests the essential role of miRNAs in HCC development, metastasis, and prognosis. [14][15][16] Jiang et al 17 recently showed that microRNA-204 (miR-204), by directly targeting the nicotine adenine dinucleotide (NAD)-dependent deacetylase sirtuin 1 (SIRT1), suppresses the survival, stimulates the apoptosis, and inhibits the invasion and tumorigenesis of HCC cells. In spite of the therapeutic potential of miR-204, its level is downregulated in HCC tissues and negatively correlated with that of SIRT1.…”
Section: Introductionmentioning
confidence: 99%